Getting Started in an Area of Interest. Issue 2 (1st April 2004) - Caplan, Louis R.
Abstract : How does a physician become acknowledged as an expert in a particular area? This question is often asked by trainees and junior staff physicians because the mountain seems very high from the bottom. I should emphasize at the outset that it is very important to have at least one area of special interest, knowledge and ability. As William James, the philosopher, emphasized, he would be upset if someone denigrated his ability as a philosopher or violinist but could not care less if he was told he was poor at chess or cooking or golf. Having a special interest and collecting information and improving in that area of interest gives direction to the day's activities and helps an individual's sense of accomplishment and self-worth. I think it often happens like this. Early in their career a doctor is struck with an individual encounter or event that stimulates an interest in a